Foam injection molding of poly(lactic) acid: Effect of back pressure on morphology and mechanical properties. Issue 48 (16th July 2015) - Volpe, Valentina; Pantani, Roberto; Pantani, Prof. Roberto; Turng, Prof. Lih‐Sheng
ABSTRACT Foam injection molding is a processing technology applied to produce a plastic part of a well‐defined shape, containing a significant fraction of voids and thus consuming less material without sacrificing mechanical properties. This technology is particularly interesting for biodegradable polymers and in particular for poly(lactic acid), PLA, since it can be adopted to save material and to avoid thermal degradation due to its high viscosity at high shear rates, which requires high temperatures in traditional injection molding process. In this work a traditional injection molding machine, modified just in the cylinder to allow the gas injection, was adopted to obtain foam injection molding of a PLA grade. In particular, the effect of back pressure on foaming was assessed. Back pressure is the pressure imposed at the back of the screw when it is returning back to prepare a new amount of material to be injected (batching phase) and thus is particularly relevant in the formation of the polymer−gas mixture. It was shown that on increasing the back pressure the percentage of foaming agent inside the injection chamber is smaller, and thus foaming is less effective. The obtained samples were characterized as far as density and mechanical properties are concerned and it was found that it was possible to reduce the density of about 25% without a significant loss of mechanical properties. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42612.